Famous Scholars Who Contributed To The Development Of The Hanafi School - Ro‘zmetov Muhammad Mustafo (Zien Journals, 2024)
The Hanafi sect was introduced by Imam Abu Hanifa. But in his time, the sect was not fully formed as a sect. His madhabib was mainly developed by his students and famous jurists who came after him and brought it to the state level. This article discusses some of the famous jurists who contributed to the development of the Hanafi school of thought.
Keywords: kufa; basra; fiqh; mazhab